Quest for Variation in Inter-Firm Influence:An Empirical Exploration - Mandal, Kaushik; Roy, Koushick (Indian Journal of Marketing, 2016)
Previous research studies have been carried out in different aspects of inter-firm influences, but no efforts have yet been taken to understand influence strategy wise variation across the countries and within a country across the industries. Hence, with an objective to fill this research gap, we primarily focused in this research in measuring the influence strategy variation among the channel participants (CPs) of USA&India, and within India, we focused on a cross section of the industries namely, water purifier, FMCGs, pharmaceutical, and cement. To maintain parity with research use to compare with the situation of USA, we estimated influence strategies by perceived reporting of CPs. Hence, samples for the present research were drawn from owners of the CP firms or their authorized representatives. We held a discussion with the executives of the leading players of the four industries namely B2B, FMCG, pharmaceutical, and cement, and based on their market share in the Southern part of West Bengal, we prepared a list of CPs. The questionnaire was sent to 317 CPs randomly drawn from four industries mentioned, but we received 219 responses. Appropriate statistical testing revealed variation of influence strategies between USA and India, and a significant association between influence strategies and industry-type. This research would be extremely helpful for organizations that are planning to deal with distribution partners of the emerging nations. In a nutshell, this research has proposed being ’glocal’ in place of ’global’ strategies.